ANALYSIS OF GENDER DIFFERENCES IN THE MAKING OF MATHEMATICAL CROSS-STITCH ART SYMBOLS AND LEARNING OUTCOMES OF HIGH SCHOOL STUDENTS - Nafida Hetty Marhaeni; Ujang Nendra Pratama; Nanang Khuzaini; Nuryadi Nuryadi; Dangin Dangin (Kwangsan: Jurnal Teknologi Pendidikan, 2023)
This study aims to determine the influence of gender differences on the making of mathematical cross-stitch art symbols and students’ learning outcomes. This study is descriptive qualitative research. The study used observation, interviews, documentation, and students’ learning outcomes tests as research instrument. This research has been conducted in the crafts subject at SMA Negeri 1 Pengasih, Kulon Progo, Yogyakarta class XI. Meanwhile, the results of midterm and final exam were used for all students of class XI. This study revealed a significant difference between male and female students when completing the cross art of mathematical symbols. Female students are found to be able to complete the art within 1 month, while male students have not been able to complete the cross stitch. Furthermore, the average scores obtained during midterm and final exam between male and female students also have quite significant differences, in which female students show higher learning outcomes than male students. It is in line with the completion of the cross-stitch assignment given in the craft subject where female students have better abilities in completing the cross-stitch art. AbstrakPenelitian ini bertujuan untuk mengetahui ada tidaknya pengaruh perbedaan gender terhadap pembuatan seni kristik symbol matematika dan hasil belajar siswa. Jenis penelitian yang digunakan dalam penelitian ini adalah penelitian deskriptif kualitatif. Adapun teknik pengumpulan data menggunakan observasi, wawancara, dokumentasi, dan tes hasil belajar siswa. Penelitian ini akan dilakukan pada mata pelajaran Prakarya di SMA Negeri 1 Pengasih, Kulon Progo, Yogyakarta kelas XI. Sedangkan secara kuantitatif digunakan hasil PTS dan PAS semua siswa kelas XI. Penelitian ini menghasilkan perbedaan yang cukup signifikan antara siswa laki-laki dan perempuan saat menyelesaikan seni kristik symbol matematik. Yang mana siswa perempuan mampu menyelesaikan seni tersebut dalam waktu 1 bulan, sedangkan siswa laki-laki belum mampu menyelesaikan seni kristik tersebut. Lebih lanjut, rata-rata skor yang diperoleh saat PTS dan PAS antara siswa laki-laki dan perempuan juga memiliki perbedaan yang cukup signfiikan, yang mana siswa perempuan memiliki hasil belajar yang lebih tinggi daripada siswa laki-laki. Hal tersebut selaras dengan penyelesaian tugas seni kristik yang diberikan pada mata pelajaran prakarya yang mana siswa perempuan memiliki kemampuan yang lebih baik dalam menyelesaikan seni kristik tersebut.